Effectiveness of Administering Warm Infusion Fluids Against Shivering Occurrence in Patients Sectio Caesarea with Spinal Anesthesia - Kurniawan, Adytia; Novitasari, Dwi; Burhan, Asmat (GLOBAL HEALTH SCIENCE GROUP, 2024)
Shivering is a common postoperative issue that can exacerbate patient discomfort and hinder recovery. This study aims to evaluate the effectiveness of administering warm intravenous fluids in reducing shivering incidence in patients undergoing cesarean section (SC) with spinal anesthesia at RSUD Dr. Soekardjo, Tasikmalaya, Indonesia. Using a quasi-experimental design with a pretest-posttest control group model, 60 patients were divided into two groups: an experimental group receiving warm intravenous fluids and a control group receiving warm blankets. The study employed non-probability purposive sampling, dividing a total of 60 respondents into two groups: the experimental group (n = 30) and the control group (n = 30). An observation sheet for research instruments. The results of this study were tested using univariate analysis and bivariate analysis, specifically the Mann-Whitney U Test. Results indicate that warm intravenous fluids are significantly more effective in reducing shivering compared to warm blankets, with a p-value of 0.000 (p<0.05) in the Mann-Whitney test. This finding suggests that the use of warm intravenous fluids can improve patient comfort and accelerate postoperative recovery.